Charlie needs a cloak - De Paola, Tomie (New York : Simon and Schuster Books for Young Readers, 1988)
A shepherd shears his sheep, cards and spins the wool, weaves and dyes the cloth, and sews a beautiful new red cloak.
A shepherd shears his sheep, cards and spins the wool, weaves and dyes the cloth, and sews a beautiful new red cloak.
Elementary School Library Collection (Bro-Dart)
ALA Notable Books
Booklist
1.9
K-3
Keywords: Hand spinning -- Juvenile literature; Hand weaving -- Juvenile literature; Dyes and dyeing -- Wool -- Juvenile literature; Cloaks -- Juvenile literature; Wool; Clothing and dress; Wool; Clothing and dress